Design of an Impulse Radiating Antenna Using a Curved TEM-Wire Fed Parabola - Donghyun Lee; Haengseon Lee; Sunmook Hwang; Jaewoon Ahn (International Journal of Antennas and Propagation)
A design procedure for a TEM-wire fed parabolic antenna is given for impulse radiation, which is suitable for low cost fabrication. A simple wire-type TEM horn and a parabolic reflector are used to achieve ultra-wide bandwidth and high directivity at the same time. Equations for parametric curves of a TEM-wire horn are presented and are used to investigate the relation among their shapes, bandwidth, and directivity. It is also found that wire separation near the focal point limits the high frequency directivity.